Faktor-faktor yang Memengaruhi Partisipasi Anggota Pada Kelompok Tani Tampirejo Makmur di Kelurahan Rowosari Tembalang Semarang - Handayani, Ikhda Fitri; Mariyono, Joko; Gayatri, Siwi (Universitas Galuh, 2025)
The success of farmer groups in achieving their goals and the welfare of their members depends on member participation. Member participation is related to the cohesiveness of the farmer group, where higher participation leads to greater cohesiveness. This study aims to: 1) Describe the participation of farmers in the Tampirejo Makmur farmer group in Rowosari, Tembalang, Semarang. 2) Describe the cohesiveness of the Tampirejo Makmur farmer group in Rowosari, Tembalang, Semarang. 3) Analyze the relationship between farmer participation and the cohesiveness of the Tampirejo Makmur farmer group in Rowosari, Tembalang, Semarang. The research was conducted from November to December 2023 in the Tampirejo Makmur farmer group. The research location was purposefully selected, considering that the Tampirejo Makmur group is a mid-level farmer group with the largest membership of 92 individuals. The research method employed was observational. The respondents were all members of the Tampirejo Makmur farmer group. The data analysis method used was quantitative descriptive analysis, scoring the responses from the research instruments, which were then statistically analyzed to determine the levels of cohesiveness and participation, as well as the relationship between the two variables. The analysis results indicated that the level of participation among members of the Tampirejo Makmur farmer group was low. Age, education level, leadership capability, socialization intensity, and external stimuli from the government or other parties influenced participation. Age and education level had no partial effect, while leadership capability, socialization intensity, and external stimuli had a partial effect on member participation. The study suggests that farmer groups should enhance collaboration with agricultural institutions to improve participation by providing relevant agricultural information.